2021
DOI: 10.1101/2021.01.02.425093
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Priming mycobacterial ESX-secreted protein B to form a channel-like structure

Abstract: ESX-1 is a major virulence factor of Mycobacterium tuberculosis, a secretion machinery directly involved in the survival of the microorganism from the immune system defence. It disrupts the phagosome membrane of the host cell through a contact-dependent mechanism. Recently, the structure of the inner-membrane core complex of the homologous ESX-3 and ESX-5 was resolved; however, the elements involved in the secretion through the outer membrane or those acting on the host cell membrane are unknown. Protein subst… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 88 publications
(117 reference statements)
1
7
2
Order By: Relevance
“…Following membrane insertion, the C-terminus could enhance oligomerization of ESAT-6, interactions with mycobacterial or host factors, or act as a bacterial sensor for contact- dependent lysis by ESX-1, or any combination of these. Putative mycobacterial factors include other ESX-1 substrates that contribute to virulence in addition to ESAT-6, such as EspA, EspE, or EspF (9, 32, 64), or oligomers of EspB and EspC which are proposed to be part of a putative extracellular secretory complex mediating contact-dependent lysis (65, 66). A systematic mutational analysis of the C terminus coupled with biochemical studies to identify mycobacterial, or possibly even host, determinants that bind to wildtype but not M93T and other in vivo deficient ESAT-6 mutants may pave the way to a fuller understanding of ESAT-6’s in vivo function.…”
Section: Discussionmentioning
confidence: 99%
“…Following membrane insertion, the C-terminus could enhance oligomerization of ESAT-6, interactions with mycobacterial or host factors, or act as a bacterial sensor for contact- dependent lysis by ESX-1, or any combination of these. Putative mycobacterial factors include other ESX-1 substrates that contribute to virulence in addition to ESAT-6, such as EspA, EspE, or EspF (9, 32, 64), or oligomers of EspB and EspC which are proposed to be part of a putative extracellular secretory complex mediating contact-dependent lysis (65, 66). A systematic mutational analysis of the C terminus coupled with biochemical studies to identify mycobacterial, or possibly even host, determinants that bind to wildtype but not M93T and other in vivo deficient ESAT-6 mutants may pave the way to a fuller understanding of ESAT-6’s in vivo function.…”
Section: Discussionmentioning
confidence: 99%
“…Galectin 8 LysoTracker Mycobacteria The C terminus of the mycobacterium ESX-1 secretion system substrate ESAT-6 is required for phagosomal membrane damage and virulence contact-dependent lysis by ESX-1, or any combination of these. Putative mycobacterial factors include other ESX-1 substrates that contribute to virulence in addition to ESAT-6, such as EspA, EspE, or EspF (9,32,64), or oligomers of EspB and EspC, which are proposed to be part of a putative extracellular secretory complex mediating contact-dependent lysis (65,66).…”
Section: Tuberculosismentioning
confidence: 99%
“…EspB, the largest PE/PPE family substrate secreted by the esx-1 system of Mycobacterium tuberculosis, is known to be a key player in mediating host cell pathogenicity. A wealth of structural information shows the architecture of the N-terminal region -PE and PPE domains comprising the YxxxD and WxG motifs respectively, a linker joining the PE/PPE domains and a helical tip (20)(21)(22)(23). However, to date, the C-terminal domain remains unstructured.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, it was observed that the inner diameter of EspB heptamer was nearly 4.5 nm, which indicated that the central channel was sufficiently large to transport other heterodimeric ESX-1 substrates such as ESAT6-CFP10 (22). This notion was further supported when more recently, a 7+1 model of EspB monomer trapped within a heptameric EspB channel was proposed for EspB 2-348 (23). The structure of EspB 1-460 and its isoforms has been extensively characterized; however, to date, our understanding of the functional role of EspB remains limited.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation